Disruptive patterns of eating behaviors and associated lifestyles in males with ADHD - Ptacek, Radek; Kuzelova, Hana; Stefano, George B; Raboch, Jiří; Sadkova, Tereza; Goetz, Michal; Kream, Richard M (Medical science monitor, 2014)
BACKGROUND: Attention deficit hyperactivity disorder (ADHD) is a neurological/behavioral disorder characterized by inattention or hyperactivity and impulsivity, or combined symptomatology. Children with ADHD are predisposed to irregular and/or impulsive eating patterns often leading to compromised physical condition. The goal of the present study was to statistically evaluate parental scoring of patterned eating behaviors and associated lifestyles within a cohort of 100 boys diagnosed with ADHD in comparison to age-matched male controls. MATERIAL AND METHODS: The study population consisted of 100 boys aged 6-10 years diagnosed with mixed type ADHD by DSM-IV criteria and 100 aged-matched healthy male control subjects. Patterns of eating behaviors and associated lifestyles were scored by structured parental interviews using a nominal rating scale. RESULTS: Interview scores indicated statistically significant differences in patterned eating behaviors in subjects with ADHD in comparison to healthy controls. Notably, subjects diagnosed with ADHD exhibited markedly diminished adherence to a traditional breakfast, lunch, and dinner schedule, which was linked to a significantly higher frequency (>5/day) of irregular eating times. In the ADHD cohort, disruptive patterns of eating behaviors were associated with diminished nutritional value of ingested food (expressed as lowered content of fruits and vegetables) and increased consumption of sweetened beverages. CONCLUSIONS: Disruptive patterns of eating behaviors, metabolically unfavorable nutritional status, and diminished physical activities of male children diagnosed with ADHD are linked to compromised growth and development and appearance of metabolic diseases in adulthood.
Keywords: Male; Vegetables; Fruit; televize; Life Style; studie případů a kontrol; Feeding Behavior; stravovací zvyklosti; počítače; Computers; Humans; zelenina; mužské pohlaví; Female; hyperkinetická porucha; kojení; Case-Control Studies; ženské pohlaví; Attention Deficit Disorder with Hyperactivity; Breast Feeding; ovoce; Television; lidé; dítě; životní styl; Child